Predicting lymphovascular invasion in clinically node-negative breast cancer detected by abbreviated magnetic resonance imaging: Transfer learning vs. radiomics - Feng, Bao; Liu, Zhuangsheng; Liu, Yu; Chen, Yehang; Zhou, Haoyang; Cui, Enming; Li, Xiaoping; Chen, Xiangmeng; Li, Ronggang; Yu, Tianyou; Zhang, Ling; Long, Wansheng (Frontiers in Oncology, 2022)
Objective To compare the performance of abbreviated breast magnetic resonance imaging (AB-MRI) based transfer learning (TL) algorithm and radiomic analysis for lymphovascular invasion (LVI) prediction in patients with clinically node-negative invasive breast cancer (IBC). Methods Between November 2017 and October 2020, 233 clinically node-negative IBCs detected by AB-MRI were retrospectively enrolled. One hundred and thirty IBCs from center 1 (37 LVI-positive and 93 LVI-negative) were assigned as the training cohort and 103 from center 2 (25 LVI-positive and 78 LVI-negative) as the validation cohort. Based on AB-MRI, a TL signature (TLS) and a radiomics signature (RS) were built with the least absolute shrinkage and selection operator (LASSO) logistic regression. Their diagnostic performances were validated and compared using areas under the receiver operating curve (AUCs), net reclassification improvement (NRI), integrated discrimination improvement (IDI), decision curve analysis (DCA), and stratification analysis. A convolutional filter visualization technique was used to map the response areas of LVI on the AB-MRI. Results In the validation cohort, compared with RS, the TLS showed better capability in discriminating LVI-positive from LVI-negative lesions (AUC: 0.852 vs 0.726, P < 0.001; IDI = 0.092, P < 0.001; NRI = 0.554, P < 0.001). The diagnostic performance of TLS was not affected by the menstrual state, molecular subtype, or contrast agent type (all P > 0.05). Moreover, DCA showed that the TLS added more net benefit than RS for clinical utility. Conclusions An AB-MRI based TLS was superior to RS for preoperative LVI prediction in patients with clinically node-negative IBC.